Peran Ijtihad Dalam Pembentukan Undang-Undang Syariah di Aceh - Reza Enma Monisa; Abdul Hafiz Habibi; Ahmad Syufi Kholis; Muhammad Zaki Maulana; Faqih Usman Muhammadi (Albayan Journal of Islam and Muslim Societies, 2025)
This study discusses the role of ijtihad in the formation of Sharia legislation in Aceh. As a region with special authority in the implementation of Islamic law, Aceh requires a legal foundation that can respond to social developments and the needs of modern society. Ijtihad serves as an important instrument in formulating qanun because it functions to derive law from the Qur’an and Sunnah in a contextual manner and to align it with the principles of maqashid al-shariah. This research is a library study using a normative or doctrinal legal approach. Data were collected through a review of relevant literature, books, journals, and laws and regulations, then analyzed qualitatively-descriptively through content analysis. The findings show that ijtihad has a strategic role in the formation of Sharia legislation in Aceh because it can produce law that is flexible, relevant, and oriented toward public benefit. Without ijtihad, Sharia law risks becoming rigid and difficult to adapt to the dynamics of society. Therefore, ijtihad is an important foundation in Sharia legislation in Aceh.